Pengaruh Penyuluhan dengan Media Film terhadap Health Belief Model Aktivitas Fisik pada Siswa/I SMP PGRI 363 Pondok Petir - Salwa Octavia; Rifki Luthfiyan Ramadhan; Maudy Mutiarahman; Luqman Effendi (Jurnal Kesehatan Amanah, 2026)
Adolescents have low levels of physical activity, one of which is caused by poor perceptions of the components of the Health Belief Model (HBM), while a sedentary lifestyle increases the risk of long-term health problems. This study aims to describe the HBM (perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, and cues to action) in students before counseling, and analyze the differences in HBM (perceived susceptibility, perceived severity, perceived benefits, perceived barriers) after counseling with film media. The study used a quasi-experimental design with a cross-sectional approach, involving 51 eighth-grade students of SMP PGRI 363 Pondok Petir who were selected using a total sampling technique. Data were collected using pre-test and post-test questionnaires, then analyzed descriptively using the median as the cut-off point. The results showed an increase in all four HBM constructs evaluated: perceived susceptibility increased by 50.0% (median 14 to 21), perceived severity increased by 44.4% (18 to 26), perceived benefits increased by 44.0% (25 to 36), and perceived barriers increased by 54.5% (11 to 17). Before the counseling, the majority of students were in the medium category for self-efficacy (65%) and cues to action (96%), but these two constructs were not re-evaluated after the counseling. Further research is needed to fully measure the increase in students' HBM perceptions of physical activity through film media.